2018
DOI: 10.1039/c8ta02059k
|View full text |Cite
|
Sign up to set email alerts
|

The use of metal–organic frameworks for CO purification

Abstract: Metal organic frameworks (MOFs) as adsorbents present a potentially cost effective and energy saving alternative to current technologies used to purify carbon monoxide (CO), a reagent in numerous industrial processes. This review compares the different mechanisms involved in CO adsorption in MOFs, highlighting the desired chemical and structural features for this process. An outlook on future directions for research on MOFs for CO adsorption is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 151 publications
1
76
0
Order By: Relevance
“…Here, Cu–C bonds are formed after the interaction of the CuCl-doped CXs and CO molecules. 32 The introduction of Cu + into CX can improve the CO adsorption capacity considerably and hardly affect the desorption capacity of samples. The high CO adsorption capacity of CuCl-doped CXs benefits from the combination of physical and chemical adsorption, whereas CXs and AC can only depend on physical adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Here, Cu–C bonds are formed after the interaction of the CuCl-doped CXs and CO molecules. 32 The introduction of Cu + into CX can improve the CO adsorption capacity considerably and hardly affect the desorption capacity of samples. The high CO adsorption capacity of CuCl-doped CXs benefits from the combination of physical and chemical adsorption, whereas CXs and AC can only depend on physical adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…2 MOFs have shown the most promising performance to date, 6 recording the highest CO adsorption uptakes and theoretical CO/X selectivities (where X ¼ H 2 , N 2 and CH 4 ). 5,7 MOFs are formed by organic linkers coordinating to metal nodes (or polynuclear clusters). 8 Their metal sites can provide coordinatively unsaturated metal sites, also known as openmetal sites, which have an affinity for CO. 5 Hence, the best performing MOFs are highly dependent on the MOFs' metal sites as they determine the metal-CO bond strength through both s-bond formation and p-backdonation.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 MOFs are formed by organic linkers coordinating to metal nodes (or polynuclear clusters). 8 Their metal sites can provide coordinatively unsaturated metal sites, also known as openmetal sites, which have an affinity for CO. 5 Hence, the best performing MOFs are highly dependent on the MOFs' metal sites as they determine the metal-CO bond strength through both s-bond formation and p-backdonation. 9 A comprehensive study by Bloch et al reported high CO capacities and CO/H 2 and CO/N 2 selectivities for MOF-74 (also known as CPO-27 or M 2 (DOBDC), DOBDC ¼ 2,5-dioxido-1,4-benzenedicarboxylate).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations